(untitled) (Research, Society and Development, 2022)
Arboviruses are defined as diseases transmitted to vertebrate hosts through arthropod vectors. The objective of this study was to describe the role of Nursing inserted in Primary Health Care in the control of arboviruses. This was an integrative review, using the following databases: Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO), using the descriptors "Primary Health Care", "Arboviruses", "Dengue", " Chikungunya fever” and “Zika virus infection”, using the booleans AND and OR. The final sample consisted of 16 scientific articles, having as inclusion criteria those available in Portuguese, dated in the last 5 years and that met the objective of the study. It is noticed that arboviruses have a great potential for dispersion, an ability to adapt to new environments and hosts, which allows the emergence of extensive epidemics and the occurrence of severe cases. Thus, among the different functions of the nursing professional as a member of the Primary Care health team is the administration and management of the actions to be carried out. It is concluded that the circulation of arboviruses characterizes a daily challenge to public health and that nursing professionals working in Primary Health Care establish health education actions to control these diseases.